686. Comparing Treatments of Methicillin-Resistant Staphylococcus aureus Infective Endocarditis by People Who Inject Drugs. (4th December 2021) - Rebold, Nicholas; Alosaimy, Sara; Lagnf, Abdalhamid M; Holger, Dana; Rybak, Michael J
Abstract: Background: People who inject drugs (PWID) are at high risk for infective endocarditis (IE) with high-mortality pathogens such as methicillin-resistant Staphylococcus aureus (MRSA). Stigma against PWID may cause differences in treatment and outcomes between these patients infected with MRSA IE. Methods: Single center retrospective cohort study from August 2006 to February 2021 that includes adult patients diagnosed with IE. Primary outcomes included 90-day all-cause mortality, 60-day MRSA recurrence, 60-day readmission, and hospital length of stay (LOS). Statistical analysis was performed by chi-square, t-test, and Mann-Whitney-U as appropriate. Results: A total of 214 patients were diagnosed with MRSA IE; 89 PWID and 125 non-PWID. The mean (SD) age was 47.4±12.4 years (PWID) vs 59.3 ±16.0 years (non-PWID) (p< 0.001). Patients were primarily male (56%), but differed in terms of race 34% African-American (AA) (PWID) vs 66% AA (non-PWID) (p< 0001). Mean APACHE II scores differed between groups: 16(±9.9) (PWID) vs 19(±8.1) (non-PWID) (p< 0.008). Among patients who cleared bacteremia, mean (SD) duration was 5.7(±3.9) days and was not significant between groups (p< 0.64). Valve-type was 93% native and 7% prosthetic and not different between groups (p< 0.16). Infectious Diseases consult did not differ at 96% overall (p< 0.31), but pursuit of source control nearly reached significance at 27% for PWID vs 41% non-PWID (p< 0.06). Similarly, use of combination therapy daptomycin and ceftaroline was nearly significant: 21% (PWID) vs 12% (non-PWID) (p< 0.09). Odds ratio of PWID and combination therapy remained non-significant after regression: 0.39(0.14-1.1, p< 0.07). Primary 90-day mortality was lower in PWID vs non-PWID (15% vs 30%) respectively (p< 0.01), but did not differ in 60-day MRSA recurrence (p< 1.0) at 9%, 60-day readmission (p< 1.0) at 33%, or median LOS (IQR) (p< 0.46) at 15 (10-24) days overall. Conclusion: While PWID are significantly younger, less critically ill, and have lower mortality compared to non-PWID, they have similar LOS, MRSA recurrence, and readmission rates. Analyses suggest a potential difference in the pursuit of source control and combination therapy among PWID, however more studies may be needed to achieve significance. Disclosures: Michael J. Rybak, PharmD, MPH, PhD, Paratek Pharmaceuticals (Research Grant or Support)